Proceedings of the 3rd International Conference on Technical Debt 2020
DOI: 10.1145/3387906.3388624
|View full text |Cite
|
Sign up to set email alerts
|

How junior developers deal with their technical debt?

Abstract: Technical debt is a metaphor that measures the additional effort needed to continue to add more features in a software due to its inherent decrease in code quality. Most software systems suffer from technical debt at some point so that dedicated tools and metrics have been developed to monitor such debt. Alongside tools, appropriate engineering practices must be put in place by the development team to keep that debt at an acceptable level. In this empirical study, we observed and surveyed Scrum development tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…There are also external factors that can affect how developers remediate technical debt, such as using tools. For example, Gilson et al [19] found that junior developers tend to use static analysis tools to value composite quality indicators (e.g., maintainability, reliability in SonarQube), even if they do not fully understand their meaning. However, Ernst et al [20] conducted a survey with 1831 participants, primarily software engineers and architects, and found that the lack of tool support for accurately managing and tracking architectural sources of debt is a key issue and remains a gap in practice.…”
Section: Related Workmentioning
confidence: 99%
“…There are also external factors that can affect how developers remediate technical debt, such as using tools. For example, Gilson et al [19] found that junior developers tend to use static analysis tools to value composite quality indicators (e.g., maintainability, reliability in SonarQube), even if they do not fully understand their meaning. However, Ernst et al [20] conducted a survey with 1831 participants, primarily software engineers and architects, and found that the lack of tool support for accurately managing and tracking architectural sources of debt is a key issue and remains a gap in practice.…”
Section: Related Workmentioning
confidence: 99%
“…There are also external factors that can affect how developers remediate technical debt, such as using tools. For example, Gilson et al [19] found that junior developers tend to use static analysis tools to value composite quality indicators (e.g., maintainability, reliability in SonarQube), even if they do not fully understand their meaning. However, Ernst et al [20] conducted a survey with 1,831 participants, primarily software engineers and architects, and found that the lack of tool support for accurately managing and tracking architectural sources of debt is a key issue and remains a gap in practice.…”
Section: Related Workmentioning
confidence: 99%
“…However, where tentative conclusions are still acceptable, α ≥ 0.67 is the lowest conceivable limit [53]. 19 https://github.com/jieshanshan/ist-si-sftd 32GB of RAM.…”
Section: Associated Dataset and Replicationmentioning
confidence: 99%
“…However, although it has a growing community, most package contributors are not software engineers by training [15], and only a few of them are mindful of the inner concepts of the language [18]. This lack of formal programming training can lead to lower code quality [19].…”
Section: Introductionmentioning
confidence: 99%